Competitiveness in innovative software and information technology enterprises - Mosquera Abadia, Henry Alberto; Millan Solarte, Julio Cesar (Cuadernos de Administración, 2013)
This article presents the results of the study “Measuring the Business Competitiveness Financial Indicators” conducted by the Research Group Solvency and Financial Risk at Universidad del Valle, on the universe of companies reporting their financial statements to the Superintendencia de Sociedades de Colombia from 2007 to 2009; specifically, the companies in the software and computer technology field. These results were used for classification and SIREM database of the Superintendency in question and used the nonparametric BCC Data Envelopment Analysis (DEA) model. The results show 13 companies with technically efficient use of resources taken as inputs for 2007, four companies in 2008 were efficient, and 10 effective companies for 2009. The efficiency analysis considered three variables as input and four outputs.